2013
DOI: 10.1007/s00394-013-0622-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of flavonoids on oxidative stress and mineral contents in the retinoic acid-induced bone loss model of rat

Abstract: These results suggest that the dietary flavonoids could reduce retinoic acid-induced oxidative stress and bone loss and that flavonoids may be useful therapeutics for prevention of skeletal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 37 publications
2
56
0
3
Order By: Relevance
“…Orsolic et al (2014) reported the inverse results in that the rats’ body weight decreased after treatment with 80 mg/kg body weight retinoic acid and most rats died before the end of the experiment [2]. Nonetheless, no mortality and weight loss were observed in this study by retinoic acid treatment at the same dose.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Orsolic et al (2014) reported the inverse results in that the rats’ body weight decreased after treatment with 80 mg/kg body weight retinoic acid and most rats died before the end of the experiment [2]. Nonetheless, no mortality and weight loss were observed in this study by retinoic acid treatment at the same dose.…”
Section: Resultsmentioning
confidence: 50%
“…There is a negative imbalance between bone formation and bone resorption resulting in bone loss and the etiology can be multifactorial, with contributions from diet and lifestyle, genetics like sex and ethnicity, and other medical conditions [2]. Postmenopausal osteoporosis accounts for a large proportion of osteoporosis in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies also showed that retinoic acid causes constant decrease of BMD in a short period of 1-3 weeks [20]. All these findings demonstrated that shortterm effects of retinoic acid could act as an appropriate revulsive of osteoporosis [22].…”
Section: Introductionmentioning
confidence: 96%
“…A flavonoid rich diet is reported to induce the expression of antioxidative enzymes in various cell types [3538]. However, this induction of the expression of antioxidative enzymes can only be reached, when flavonoids are consumed at high doses over a long period of time.…”
Section: Discussionmentioning
confidence: 99%